Trehalose-6-Phosphate: Connecting Plant Metabolism and Development - Ponnu, Jathish; Wahl, Vanessa; Schmid, Markus (Frontiers in Plant Science, 2011)
Beyond their metabolic roles, sugars can also act as messengers in signal transduction. Trehalose, a sugar found in many species of plants and animals, is a non-reducing disaccharide composed of two glucose moieties. Its synthesis in plants is a two-step process, involving the production of trehalose-6-phosphate (T6P) catalyzed by trehalose-6-phosphate synthase (TPS) and its consecutive dephosphorylation to trehalose, catalyzed by trehalose-6-phosphate phosphatase (TPP). T6P has recently emerged as an important signaling metabolite, regulating carbon assimilation and sugar status in plants. In addition, T6P has also been demonstrated to play an essential role in plant development. This review recapitulates the recent advances we have made in understanding the role of T6P in coordinating diverse metabolic and developmental processes.